Research on the Impact of Digital Transformation on the Performance of Commercial Banks from the Perspective of Management Innovation: Empirical Analysis based on the Shanghai and Shenzhen A-Share Listed Banks - Cheng, Zhengqiu (International Journal of Computer Science and Information Technology, 2025)
Taking the 2011-2021 A-share listed banks in Shanghai and Shenzhen as the research sample, the impact of digital transformation on the financial performance of commercial banks is explored from the micro level. The study has found that the digital transformation has significantly improved the financial performance of commercial banks, and this conclusion is still valid after the robustness test. Mechanism analysis found that digital transformation can improve the management innovation of commercial banks, and then improve the financial performance of commercial banks. The heterogeneity analysis shows that digital transformation improves financial performance better than in non-state banks, but not significant, and improves financial performance better in small banks and significantly than in large banks.